A Frontal Lobe Meningioma in a Child Leading to Visual Loss - Nedime Sahinoglu-Keşkek; Gokhan Soker; Şakir Özgür Keşkek; Sehire Sahinoglu; Figen Unal; Fikret Unal; Selim Cevher (Case Reports in Ophthalmological Medicine)
Objective. Meningiomas are benign primary meningeal tumors and are seen rare in children and adolescents. Clinical Presentation and Intervention. A 15-year-old Turkish boy reported a 1-month history of headache and blurred vision in both eyes. His visual acuity was 0.3 in both eyes with papilledema. Magnetic resonance imaging showed a 77×97×77 mm intracranial-extra-axial frontal lesion which compresses the chiasm. He was diagnosed with intracranial meningioma and referred to neurosurgery clinic. Conclusion. Ophthalmologists should be aware of the fact that papilledema and low vision can be caused by an intracranial tumor which compresses optic chiasm.